Outcomes of giant cell tumors around the foot and ankle: A pilot study - Elsayed, Moataz A.; Shamma, Ahmed A.; Hasan, Mahmoud Seddik; Abdelkader, Mohamed G.; A Ibrahim, Mohamed Adel (Acta Biomedica Atenei Parmensis, 2025)
Objective: The giant cell tumor (GCT) of bone is a benign primary bone tumor that frequently exhibits aggressive behavior and a propensity for local recurrence, which is influenced by the treatment modality and the tumor’s local characteristics. This study aimed to assess the efficiency, safety, recurrence and functional outcome of using the technique of extended curettage and cementation for the surgical management of GCT around the foot and ankle. Methods: Nine male and three female patients who had GCT around their ankle or foot were included. The average age was 33 years, with an average follow-up period of 12 months. Three patients had lesions in the distal tibia, one patient had lesions in the lateral malleolus, four patients had lesions in the talus, three patients had lesions in the calcaneus, and the remaining patient had lesions in the 1st metatarsal bone. Results: All patients experienced outstanding functional and satisfying results. No recurrence or damage to adjacent tissues was noted, and no serious intraoperative or postoperative problems were reported. There is a highly significant improvement of the American Orthopaedic Foot and Ankle Society (AOFAS) score with an average of 27.92 ± 5.42, which increased from 69.17 ± 5.97 preoperatively to 97.08 ± 3.34 postoperatively. Conclusion: Based on our study results, the technique of extended curettage and cementation is a valid option for treating GCT because, in contrast to cement’s mechanical and cytotoxic properties, it provides exceptional safety results, ease of handling, and positive post-operative outcomes with no functional problems or recurrences.